SYSTEMATIC LITERATURE REVIEW: PERAN HR ANALYTICS DALAM MENINGKATKAN KINERJA GURU - Agustina Ramadhianti; Kristiningsih Kristiningsih; Henny Suharyati (STKIP Pesisir Selatan, 2026)
This study aims to examine the role of HR Analytics in improving teacher performance, as well as to identify supporting factors, implementation mechanisms, and challenges in its application within educational organizations. This study employs a Systematic Literature Review (SLR) to explore the contribution of Human Resource Analytics (HR Analytics) to teacher performance. The review follows the PRISMA 2020 framework by analysing literature published between 2020 and 2025, sourced from Scopus, Google Scholar, DOAJ, SpringerOpen, MDPI, UNESCO, OECD, and the World Bank. A total of 30 open-access articles were selected through stages of identification, screening, eligibility assessment, and inclusion. The findings reveal four key themes: (1) HR Analytics enhances data-driven decision-making; (2) teachers’ digital competence is a critical prerequisite for maximizing the impact of HR Analytics on performance; (3) performance management systems (PMS) serve as a linkage mechanism between data, feedback, and performance improvement; and (4) implementation barriers include infrastructure readiness, data literacy, information governance, and organizational resistance. These results indicate that HR Analytics cannot function effectively in isolation but must be integrated with strengthened digital competencies, supportive school leadership, and adaptive performance management systems. The study implies that schools and policymakers need to foster an evidence-based human resource management culture to sustainably improve teacher performance.